Correlations of serum histone deacetylase 3 and thrombospondin-1 levels with cardiac function grades, ventricular remodeling, and prognosis in patients with chronic heart failure - Jiange Cheng; Tao Cheng (Journal of Cardiothoracic Surgery, 2025)
Abstract Background This study aims to analyze the relations of serum Histone Deacetylase 3 (HDAC3) and Thrombospondin-1 (TSP-1) levels to cardiac function grades, ventricular remodeling, and prognosis of patients with chronic heart failure (CHF). Methods We conducted a retrospective analysis of 128 enrolled CHF patients, with 102 healthy individuals as controls. Baseline data and two-year follow-up records were collected to assess prognosis. Serum levels of HDAC3 and TSP-1 were measured using ELISA, and their correlations with ventricular remodeling indicators such as LVEF, LVEDD, LVFS, BNP, NT-proBNP, and cTnI were analyzed using Pearson’s correlation coefficient. Results No significant differences were observed among participants in terms of age, gender, BMI, comorbidities, smoking history, and drinking history. CHF patients exhibited significantly reduced LVEF and LVFS, while LVEDD, BNP, NT-proBNP, cTnI levels, and serum levels of HDAC3 and TSP-1 were markedly elevated. It was found that serum levels of HDAC3 and TSP-1 increased with worsening cardiac function. Both of them correlated significantly with ventricular remodeling indicators, and their elevation was an independent risk factor for poor prognosis in CHF patients. Conclusion Serum levels of HDAC3 and TSP-1 are elevated in CHF patients, exhibiting significant correlations with ventricular remodeling indicators. Combined detection of these two markers may assist in predicting poor prognosis in CHF patients.